2004
DOI: 10.1210/er.2002-0022
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Complications of Acromegaly: Epidemiology, Pathogenesis, and Management

Abstract: This review focuses on the systemic complications of acromegaly. Mortality in this disease is increased mostly because of cardiovascular and respiratory diseases, although currently neoplastic complications have been questioned as a relevant cause of increased risk of death. Biventricular hypertrophy, occurring independently of hypertension and metabolic complications, is the most frequent cardiac complication. Diastolic and systolic dysfunction develops along with disease duration; and other cardiac disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

33
1,070
4
100

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,154 publications
(1,207 citation statements)
references
References 426 publications
(560 reference statements)
33
1,070
4
100
Order By: Relevance
“…A cromegaly is a rare disease resulting from hypersecretion of growth hormone (GH) and as a consequence of insulin like growth factor-I (IGF-I), which in most cases is caused by a GH-secreting pituitary adenoma (1). Uncontrolled acromegaly is associated with increased morbidity and mortality (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…A cromegaly is a rare disease resulting from hypersecretion of growth hormone (GH) and as a consequence of insulin like growth factor-I (IGF-I), which in most cases is caused by a GH-secreting pituitary adenoma (1). Uncontrolled acromegaly is associated with increased morbidity and mortality (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…The causal effect of GH oversecretion is acromegaly or gigantism. Cardiovascular, cerebrovascular, respiratory, and metabolic diseases are potential more severe consequences (Melmed et al, 1995;Colao et al, 2004;Jenkins, 2004).…”
mentioning
confidence: 99%
“…Although the incidence of neoplasms in acromegaly is a matter of debate, numerous reports have suggested that patients are at increased risk of developing thyroid nodules and colon polyps 20 , as well as thyroid cancer 21 breast cancer 22 and colorectal cancer 23 . There are limited data in the literature concerning the adrenal involvement in acromegalic patients.…”
Section: Discussionmentioning
confidence: 99%